Стихотворения, не вошедшие в "Собрание стихотворений" - Есенин Сергей Александрович (2009)
Экземпляры: БС (20170829) / Инвентарный номер: РТШ51837 / Сис.шифр: Р2 / Авт.знак: Е 82 / ГРНТИ: 17.82.10 / ББК: 84(2)